Centrifugal Force Boosts Self‐Assembly of Gradient Lattice Photonic Crystals - Jingying Zhang; Xinye Wang; Yexiaotong Zhang; Jiaxing Yang; Xuelei Han (Advanced Photonics Research)
Gradient photonic crystals, compared to traditional photonic crystals, possess broader photonic bandgaps and more flexible arrangement structures. This article proposes a centrifugal force‐driven self‐assembly method for controllable construction of gradient lattice photonic crystals. This method uses chemical synthesis to prepare size‐controllable core–shell nanoparticles and applies centrifugal force to assist the arrangement of the nanoparticles in gradient lattice. Theoretical calculations indicate that the centrifugal potential energy distribution and the relative centrifugal force are proportional to the centrifugal speed and centrifugal radius. By controlling the centrifugal potential energy distribution of the prepared core–shell SiO2@Fe3O4 nanoparticles in the centrifuge tube, a gradient lattice photonic crystal exhibiting a rainbow structural color from purple to red is obtained. The experimental results closely align with the theoretical predictions. The proposed approach to build gradient lattice photonic crystals has great application potential in the fields of optical switches, optimization of light extraction efficiency, and low‐loss light transmission.